Morphological characterisation of glial and neuronal tau pathology in globular glial tauopathy (Types II and III). (6th November 2019) - Tanaka, H.; Toyoshima, Y.; Kawakatsu, S.; Kobayashi, R.; Yokota, O.; Terada, S.; Kuroda, S.; Miura, T.; Higuchi, Y.; Otsu, H.; Sanpei, K.; Otani, K.; et al.
Abstract : Aims: Globular glial tauopathy (GGT) is a new category within the 4‐repeat tauopathies that is characterised neuropathologically by tau‐positive globular glial inclusions (GGIs), namely, globular oligodendrocytic and astrocytic inclusions (GOIs and GAIs). Occurrence of tau‐positive neuronal cytoplasmic inclusions (NCIs) is also a feature. GGT is classified into three pathological subtypes (Types I, II and III). We studied the tau pathology in 6 cases of GGT (Type II, n = 3; Type III, n = 3), with special reference to GAIs and NCIs. Methods: Neuropathological examinations were conducted, along with immunohistochemistry, morphometry and three‐dimensional imaging, and biochemical and genetic analysis of tau. Results: The cortical GAIs in Type II and those in Type III were distinguishable from each other. In the motor cortex, GAIs were much more numerous in Type III than in Type II. Prominent occurrence of perikaryal globular structures was a feature of GAIs in Type III. By contrast, prominent occurrence of radiating process‐like structures was a feature of GAIs in Type II. Overall, the GAIs were significantly smaller in Type III than in Type II. NCIs were divisible into three subgroups in terms of shape: diffuse granular, thick cord‐like, and round/horseshoe‐shaped structures. In all cases, NCIs were a feature of the upper and lower motor neurons. Interestingly, the round/horseshoe‐shaped NCIs were observed only in Type III cases. Conclusions: These findings, which characterised GAIs and NCIs, indicated that Type II and Type III constitute two distinct pathological subtypes, and also further strengthen the concept of GGT as a distinct entity.